Early biofilm and streamer formation is mediated by wall shear stress and surface wettability: A multifactorial microfluidic study. Issue 4 (16th August 2022) - Chun, Alexander L. M.; Mosayyebi, Ali; Butt, Arthur; Carugo, Dario; Salta, Maria
Abstract: Biofilms are intricate communities of microorganisms encapsulated within a self‐produced matrix of extra‐polymeric substances (EPS), creating complex three‐dimensional structures allowing for liquid and nutrient transport through them. These aggregations offer constituent microorganisms enhanced protection from environmental stimuli—like fluid flow—and are also associated with higher resistance to antimicrobial compounds, providing a persistent cause of concern in numerous sectors like the marine (biofouling and aquaculture), medical (infections and antimicrobial resistance), dentistry (plaque on teeth), food safety, as well as causing energy loss and corrosion. Recent studies have demonstrated that biofilms interact with microplastics, often influencing their pathway to higher trophic levels. Previous research has shown that initial bacterial attachment is affected by surface properties. Using a microfluidic flow cell, we have investigated the relationship between both wall shear stress (τw ) and surface properties (surface wettability) upon biofilm formation of two species ( Cobetia marina and Pseudomonas aeruginosa ). We investigated biofilm development on low‐density polyethylene (LDPE) membranes, Permanox® slides, and glass slides, using nucleic acid staining and end‐point confocal laser scanning microscopy. The results show that flow conditions affect biomass, maximum thickness, and surface area of biofilms, with higher τw (5.6 Pa) resulting in thinner biofilms than lower τw (0.2 Pa). In addition, we observed differences in biofilm development across the surfaces tested, with LDPE typically demonstrating more overall biofilm in comparison to Permanox® and glass. Moreover, we demonstrate the formation of biofilm streamers under laminar flow conditions within straight micro‐channels. Abstract : We used a microfluidic platform to investigate biofilm development by applying four different wall shear stresses simultaneously and tested three different surfaces with varying hydrophobicity. Our key results showed that surface wettability played a role in biofilm formation for Cobetia marina and Pseudomonas aeruginosa at low shear stress. However, this was minimized as the shear stress increased. Biofilm streamers were observed at the highest shear stress.